THE ROLE OF BEHAVIORAL BIASES IN STOCK MARKET VOLATILITY (International Journal of Food and Nutritional Sciences, 2021)
The role of behavioral biases in stock market volatility represents a significant shift from traditional economic theories, which posit that markets are efficient and driven by rational decision-making. Behavioral finance challenges this view by highlighting how cognitive distortions and psychological tendencies impact investor behavior and market dynamics. This study explores how various behavioral biases contribute to stock market volatility, offering a nuanced understanding of market fluctuations. Overconfidence, one of the primary biases, leads investors to overestimate their ability to predict market movements, resulting in excessive risk-taking and heightened trading activity. Loss aversion, another critical bias, causes investors to weigh losses more heavily than gains, often leading to irrational holding of depreciating assets and exacerbating market downturns. Herding behavior further amplifies volatility as investors follow the crowd, creating momentum-driven price swings that disconnect from fundamental values.Anchoring bias and confirmation bias also play significant roles in stock market volatility. Anchoring causes investors to rely too heavily on initial information, leading to delayed reactions to new data. Confirmation bias leads investors to seek information that supports their pre-existing beliefs, reinforcing erroneous investment decisions and contributing to price distortions. These biases disrupt the assumption of market efficiency by introducing irrational elements into investor behavior, leading to price movements that deviate significantly from intrinsic values. The resulting volatility reflects a market influenced by psychological factors rather than purely rational analysis. Understanding these biases is crucial for improving market predictions and developing strategies to mitigate their impact on financial stability. This exploration highlights the importance of integrating psychological insights into financial models to better grasp and manage market volatility.